2017
DOI: 10.1111/are.13378
|View full text |Cite
|
Sign up to set email alerts
|

Determination and transferability of plasmid-mediated antibiotic resistance genes of the bacteria isolated from rainbow trout

Abstract: Antibiotic resistance and the presence of resistance genes (ARGs) were investigated in the bacteria isolated from rainbow trout (Oncorhynchus mykiss) from different trout farms located in Turkey. The most frequent types of antibiotic resistance were towards β‐lactams (cephalothin [70% of bacterial isolates], amoxicillin [63%], ampicillin [62%], ticarcillin [56%], aztreonam [51%]), macrolide [erythromycin, 68%] and sulphonamide [sulphamethoxazole, 51%]. Of bacterial isolates, 51% were multiple drug resistant (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
2
24
1
Order By: Relevance
“…Contrary to our study, Capkin et al . () found that C . freundii, a rainbow trout isolate, was susceptible to erythromycin.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Contrary to our study, Capkin et al . () found that C . freundii, a rainbow trout isolate, was susceptible to erythromycin.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to our study, it was found that A. hydrophila and A. sobria , an intestinal isolates of rainbow trout, were susceptible to chloramphenicol, while they showed resistance of 25–73% to streptomycin and erythromycin (Capkin et al . ). Likewise, it was reported that there were strains resistant to streptomycin among A. veronii strains isolated from trout farms and strains resistant to erythromycin isolated from tilapia fish and aquaculture ambient (Akinbowale et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations